Diagnóstico situacional em escolas estaduais de Minas Gerais: cenário da gestão dos documentos arquivísticos que compõem o dossiê funcional do servidor - Josias Julio de Araujo (2022)
Due to the technological advance that society experiences, the processes and procedures used in institutions tend to undergo changes. And these changes are necessary and aim to meet the new demands presented by institutions that need new tools and methodologies capable of optimizing their work routines and their Archival Document Management processes. In this context, educational institutions are included, specifically, the State Schools of Minas Gerais (EEMG) and the Archival Document Management processes adopted by them. These institutions have presented difficulties in managing their documentary collections, namely, the archival collections produced by the Personnel Department of the institution. In view of the above, so that the EEMG can meet the new contemporary context, in an optimized way, ensuring access and recovery of said collections, both by servers and by the Public Administration, it is necessary that schools choose to manage their documentary collections in a standardized. And for that, it is necessary that they implement new procedures of organization and management of Archival documents, specifically those that make up the functional dossier of the server that works in these institutions, aiming, thus, to guarantee access and recovery in a safe way to those who need it. Also, ensure that the process of creating and providing information from the server's functional dossier is being operated correctly and aligned with the relevant legislation, as well as the quality standards established by the guidelines. Thus, this research aimed to carry out a situational diagnosis to verify the existence of Archival Document Management methodologies in the Personnel Department sectors of the EEMG, specifically those that make up the server's functional dossier.To carry out the proposed research, technical visits were carried out in some EEMG located in the municipality of Santa Luzia/MG, according to a previously defined sample, in which it was possible to collect data through interviews and document analysis. In addition to the application of the questionnaire at the state level. The diagnosis made it possible to verify that currently the EEMG do not adopt a formalized methodology for the management of archival documents. These institutions currently use personal experiences for the management of their documentary collection, which is not indicated by the literature nor by the legal norms. Thus, it is believed that, through the diagnosis, such institutions can implement actions to improve the aforementioned archival document management process, meeting the demands presented with greater agility, in addition to guaranteeing security and quality to the documents.